The population biology of the sweetthorn acacia karroo in rehabilitating coastal dune forests in northern Kwazulu-Natal, South Africa - Van Aarde, Rudi J. (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1996.